The Symbolism of the Flutein Sufist Poetry - Hamad, Pakhshan Pakhshan (Humanities Journal of University of Zakho, 2018)
The Flute' is the main poem in the Mathnawi. It represents man whose life is similar to that of the flute. Jalal Aldin's Mathnawi is a spiritual training that penetrates to the depth of the soul. It also reflects a sufist's experience and was greatly adopted in Kurdish poetry. This can be seen in the poetry of Mulla Aljiziri. The flute has a history in different civilizations; it refers to the origin of man. It also reflects man's feeling of homesickness. The flute is of significant importance in Sufism and is a frequent symbol in poetry. That is why is used in Sufist religious songs and rituals.